Demonstration of a White Laser with V2C MXene‐Based Quantum Dots. Issue 24 (29th April 2019) - Huang, Dapeng; Xie, Ying; Lu, Dazhi; Wang, Zeyan; Wang, Jiyang; Yu, Haohai; Zhang, Huaijin
Abstract: Multicolor photoluminescence over the full visible color spectrum is critical in many modern science and techniques, such as full‐color lighting, displays, biological and chemical monitoring, multiband communication, etc., but the ultimate white lasing especially on the nanoscale is still a challenge due to its exacting requirements in the balance of the gain and optical feedback at different wavelengths. Recently, 2D transition metal carbides (MXenes) have emerged, with some superior chemical, physical, and environmental properties distinguishing them from traditional 2D materials. Here, a white laser with V2 C MXene quantum dots (MQDs) is originally demonstrated by constructing a broadband nonlinear random scattering system with enhanced gain. The excitation‐dependent photoluminescence of V2 C MQDs is enhanced by passivation and characterized, and their localized nonlinear random scattering is realized by the generation of excitation‐power‐dependent solvent bubbles. With the optimized excitation, the blue, green, yellow, and red light is amplified and simultaneously lased. This work not only provides a kind of promising material for white lasers, but also a design strategy of novel photonics for further applications. Abstract : A white laser is demonstrated with V2 C MXene‐based quantum dots by constructing broadband optical feedback with enhanced multicolor gain. With the optimized excitation, blue, green, yellow, and red light is amplified and simultaneously lased. This work not only provides a kind of promising material for white lasers, but also a design strategy for novel photonics for further applications.